Death comes silently - Hart, Carolyn G. (Hart, Carolyn G. Death on demand series., 2012)
When her fellow charity shop volunteer Gretchen Burkholt is murdered, Dead on Demand Mystery shop owner Annie Darling enlists the help of her husband, Max, to piece together a puzzle involving an overturned kayak, a stolen motorboat, a troubled love affair, and a reckless teenager.